2013
DOI: 10.1590/s1677-5538.ibju.2013.02.10
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Serenoa Repens, Selenium and Lycopene (Profluss®) on chronic inflammation associated with Benign Prostatic Hyperplasia: results of “FLOG” (Flogosis and Profluss in Prostatic and Genital Disease), a multicentre Italian study

Abstract: Objective: To evaluate the efficacy of Profluss® on prostatic chronic inflammation (PCI). Materials and Methods:We prospectively enrolled 168 subjects affected by LUTS due to bladder outlet obstruction submitted to 12 cores prostatic biopsy for suspected prostate cancer + 2 cores collected for PCI valuation. First group consisted of 108 subjects, with histological diagnosis of PCI associated with BPH and high grade PIN and/or ASAP, randomly assigned to 1:1 ratio to daily Profluss® (group I) for 6 months or to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 28 publications
2
44
0
1
Order By: Relevance
“…Another study showed that daily intake of 150 ml tomato juice (equal to administration of lycopene at approximately 15 mg/day) for 5 weeks can significantly reduce the serum concentration of 8-OhdG (8-hydroxy-2=-deoxyguanosine, a critical biomarker of oxidative stress) after extensive physical exercise (50). In addition, lycopene is the most effective quencher of oxygen free radicals across all of the naturally occurring carotenoids and demonstrates potential anticancer properties (35,51); the latter has been evaluated in clinical trials in several countries (52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that daily intake of 150 ml tomato juice (equal to administration of lycopene at approximately 15 mg/day) for 5 weeks can significantly reduce the serum concentration of 8-OhdG (8-hydroxy-2=-deoxyguanosine, a critical biomarker of oxidative stress) after extensive physical exercise (50). In addition, lycopene is the most effective quencher of oxygen free radicals across all of the naturally occurring carotenoids and demonstrates potential anticancer properties (35,51); the latter has been evaluated in clinical trials in several countries (52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%
“…At follow-up there were statistical significant reductions of extension and grading of flogosis (mean values of CD20, CD3, CD68, and PSA). This product may have an anti-inflammatory activity that could be of interest in the treatment of PCI in BPH [42]. …”
Section: Discussionmentioning
confidence: 99%
“…The latter was administered alone, or in the form of a combined tablet preparation (Profluss ® ; Konpharma, Rome, Italy) including S. repens (640 mg/day), lycopene (10 mg/day) and selenium (100 μg/day) (17,18). …”
Section: Methodsmentioning
confidence: 99%